Effect of inlet pipe design on self-cleaning ability of a circular tank in RAS - Zhang, Yuji; Yang, Xu; Hu, Jiajun; Qu, Xiaoyu; Feng, Dejun; Gui, Fukun; Zhu, Fang (Frontiers in Marine Science, 2023)
To improve the water reuse efficiency of circular recirculating aquaculture tanks in Recirculating Aquaculture Systems (RAS) this research investigated the effect of inlet pipe deployment distance d (the distance between the stream tube hole and the tank wall) and the inlet pipe deployment angle α (the acute angle between the inlet pipe jetting direction and the nearest tank wall) on the self-cleaning ability of the circular aquaculture tank under dual and single inlet pipe designs. First, waste collection experiments were conducted to figure out the preferable inlet pipe design based on the efficiency of waste collection. Then, flow field measurement experiments were carried out employing the Particle Image Velocimetry (PIV) technique to measure the flow field in the near bottom layer of the tank, and the essential mechanism of the inlet pipe deployment on the waste collection was explored by analyzing the flow field and the corresponding hydrodynamic characteristic indicators, such as the average flow velocity (vavg), the uniformity coefficient of water flow (DU50), and the water resistance coefficient (Ct). The results indicate that the variations of waste movement, flow filed and hydrodynamic indicators are consistent in both designs of dual inlet and single inlet, and merely differ in the absolute value. Based on the comprehensive analysis, the optimal performance of self-cleaning can be obtained at α=0°~10°, 20°~30°, 40°~50° for d=1/2 r, 1/4 r, and 1/50 r, respectively. At the same flow rate condition, the jetting velocity of the inlet pipe in the single inlet pipe design is significantly greater than that in the dual inlet pipe design, and the hydrodynamic characteristics of the waste collection are better. Therefore, in circulating water aquaculture production, it is recommended to design the inlet pipe in a similar aquaculture tank to the single inlet pipe with d=1/4 r, α=20°~30°, thus improving the self-cleaning ability of the aquaculture tank. The study results also provide a reference for adjusting the inlet pipe in circular recirculating aquaculture tank.